Bridging Economic and Social Goals: A Systematic Analysis of the Contribution of Social Entrepreneurship to Inclusive Development - Debi Septiani; Muhammad Distian Andi Hermawan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Inclusive development is becoming a key paradigm on the global development agenda as awareness grows that economic growth is not automatically able to reduce poverty, inequality, and social exclusion. In that context, social entrepreneurship emerged as an alternative approach that integrates economic and social goals through sustainable social value creation. However, the contribution of social entrepreneurship to inclusive development is still variously understood and has not been comprehensively conceptualized in the academic literature. This research aims to systematically and critically examine the contribution of social entrepreneurship to inclusive development in the last five years (2020–2024). The method used was a systematic literature review of scientific articles indexed by Scopus, Web of Science, and Google Scholar, with a total of 50 studies that met the inclusion criteria. The analysis was carried out using a thematic analysis approach to identify the concepts, contribution mechanisms, and challenges of social entrepreneurship implementation. The results of the study show that social entrepreneurship contributes to inclusive development through three main dimensions, namely economic, social, and institutional, including through the creation of inclusive jobs, increasing access to basic services, empowering marginalized communities, and strengthening multisectoral collaboration. Nonetheless, the study also identified significant challenges related to scalability, financial sustainability, and social impact measurement. These findings affirm the importance of strengthening conceptual frameworks, policy support, and the development of more systematic impact evaluation methodologies to optimize the role of social entrepreneurship in fostering inclusive and sustainable development.